PENGARUH MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR IPS DITINJAU DARI MINAT BELAJAR SISWA SEKOLAH DASAR - Erlin. K Tobamba; Eko Siswono; Khaerudin Khaerudin (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aimed at examining whether or not the teaching media gave impact to the social-subject learning outcome viewed from the students’ interest. This was an experimental study. The study employed experimental design treatment by level 2x2. The sampling participants were the fifth graders of 86 Public Elementary School, Kota Tengah and 78 Public Elementary School, Kota Tengah, Gorontalo City, academic year of 2017/2018. The participants were selected through multi stage simple random sampling. The result of this study revealed that there was a significant impact of the teaching media usage towards the social-subject learning outcome that was viewed from the students’ interest.